1961: The neutron bomb. (1st November 2020) - Dyson, Freeman
ABSTRACT: In this essay, the author says he does not believe that neutron bombs are militarily advantageous to the United States, or that they would alleviate any of the country's military problems. On the contrary, he asserts, neutron bombs, like hydrogen bombs, will in the long run only complicate human lives, increase human insecurity, and possibly facilitate the extermination of the human race.